MENUMBUHKAN KEMBANGKAN BUDAYA MENULIS KARYA ILMIAH DI ERA 5.0 PADA PESERTA DIDIK MA/SMA DAN MAHASISWA FAI UNDARIS UNGARAN KABUPATEN SEMARANG (PENULISAN ESAI SEJARAH ISLAM) - Priarni, Rina; Zamani, Badrus (Jurnal Indonesia Mengabdi, 2023)
Writing culture is a habit of conveying messages, expressing opinions and creating documentation. By writing we will have the habit of conveying systematic opinions. Writing also stimulates creativity. By writing, fresh ideas will emerge. Writing is a language skill that is very expressive and productive. It is said to be expressive because writing is the result of thoughts and feelings that can be expressed through the activity of moving fine motor skills through the strokes of our hands. Furthermore, it is said to be productive, because it is the process of producing units of language in the form of real works, until they are born in written form. Recently, the problem of the lack of student writing productivity has begun to be discussed.Both in print and electronic media. Various discussion forums were opened, such as holding seminars on writing and soft skills training on writing. This is done to "stimulate" students again to be enthusiastic about writing. It cannot be denied that writing is something urgent for students because many student activities are related to writing. Such as writing papers, research reports, scientific work, and the most important thing is writing a thesis which is the determining factor for a student to get a bachelor's degree.The aim of this activity is (1) to develop a writing culture for MA/SMA students and FAI Undaris Ungaran students. (2) help provide understanding for MA/SMA students and FAI Undaris Ungaran students about how to write essays, especially essays in Islamic History. The methods used in this activity are seminars and competitions. The seminar was carried out using a lecture, question and answer method The competition was carried out using the method of presenting essay results by the competition participants, namely, MA/SMA students and FAI Undaris Ungaran students, Semarang Regency. MA/SMA students and FAI Undaris Ungaran students after taking part in the activity had sufficiently understood the importance of writing culture in academic circles, this was proven by the participants' enthusiasm for writing Islamic History essays. It is necessary to hold the same activity at FAI Undaris Ungaran as a follow-up to this activity with another theme that supports the culture of writing among academics.